“This Is the Work of Our Hands /.../, the Japanese Work for Us” - Habinc, Mateja (Svetovi (Ljubljana), 2026)
The thematic section examines areas and aspects of handicrafts that are, at least in Slovenia, less frequently addressed in ethnology and cultural anthropology. The contributions treat handicrafts primarily as a contemporary social practice. They are interested in the social value of handicrafts and the meanings that individuals attribute to handicraft work, how handicrafts are embedded in everyday life, in questions concerning labour and entrepreneurship, and the tensions that arise between ideas about handicrafts and actual practices.
Keywords: Antropologija; contemporary handicrafts; Domača obrt; družbena praksa; economic practice; ekonomska praksa; Etnologija; Podjetništvo; Rokodelstvo; social practice; sodobno rokodelstvo